2012
DOI: 10.1186/1748-717x-7-9
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of photon and carbon ion radiotherapy in combination with chemotherapy in glioblastoma cells

Abstract: BackgroundTo evaluate the cytotoxic effect of carbon ion radiotherapy and chemotherapy in glioblastoma cells in vitro.Methods and MaterialsThe human glioblastoma (GBM) cell line U87 was irradiated with photon radiotherapy (RT) doses of 2 Gy, 4 Gy and 6 Gy. Likewise, irradiation with carbon ions was performed with single carbon doses of 0.125, 0.5, 2 and 3 Gy. Four chemotherapeutic substances, camptothecin, gemcitabine, paclitaxel and cisplatinum, were used for single and combination experiments. The assessment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
30
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(35 citation statements)
references
References 17 publications
5
30
0
Order By: Relevance
“…Additionally, having already shown that a combination of gemcitabine chemotherapy and photon irradiation benefits resectability [4], it was another aim to evaluate the effects of a combination of gemcitabine and carbon ions and in this study we have found out that additive effects, as well as a slight radiosensitizing effect in one cell line, can be achieved for this combination. Similar effects have already been confirmed at our department for glioblastoma cell lines using a combination of carbon ion irradiation and several chemotherapeutic agents including gemcitabine [27]. …”
Section: Discussionsupporting
confidence: 70%
“…Additionally, having already shown that a combination of gemcitabine chemotherapy and photon irradiation benefits resectability [4], it was another aim to evaluate the effects of a combination of gemcitabine and carbon ions and in this study we have found out that additive effects, as well as a slight radiosensitizing effect in one cell line, can be achieved for this combination. Similar effects have already been confirmed at our department for glioblastoma cell lines using a combination of carbon ion irradiation and several chemotherapeutic agents including gemcitabine [27]. …”
Section: Discussionsupporting
confidence: 70%
“…Thus, it is possible that concomitant use of cisplatin will also increase the efficacy of carbon ion radiotherapy. However, preclinical data regarding the combined effect of carbon ions and cisplatin are limited; only a few small-scale studies have been conducted (Supplementary Table 1)78910. Data from these studies are unclear as to whether the cell killing effect of carbon ions plus cisplatin is synergistic.…”
mentioning
confidence: 99%
“…The combined effect of X-rays and cisplatin has been extensively studied in the preclinical setting; however, there are no firm conclusions as to whether the effects are synergistic or purely additive because results vary widely from marked synergism to none at all (Supplementary Table 1)89101112131415161718192021. Furthermore, the presence/absence of synergism is inconsistent even between studies using the same cell lines (i.e., Agoni et al vs. Flentje et al .…”
mentioning
confidence: 99%
“…Patients with SE < 30 days had a predicted better 5-year survival rate that was greater than 20%. The effect of sequential TRT could be reduced by prolonged chemotherapy, which might result in the regeneration of drug-resistant tumor cells (Brade and Tannock, 2006;Combs et al, 2012).…”
Section: Modalities and Timing Of Radiotherapymentioning
confidence: 99%